Treatment and Outcomes of Primary Tracheal Adenoid Cystic Carcinoma: A Systematic Review - Shi Y; Xue S; Zou J (Cancer Management and Research)
Yiping Shi,1 Shan Xue,2 Jing Zou2 1Department of Nuclear Medicine, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Respirology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Jing Zou, Department of Respirology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, No. 160 Pujian Road, Shanghai, 200127, People’s Republic of China, Tel +86-021-68383093, Email drzouj@163.comAbstract: Primary tracheal adenoid cystic carcinoma (TACC) is a rare malignant tumor. This systematic review describes the treatment strategies and oncological outcomes in patients with TACC. Full-text English manuscripts published from January 1st 1960, to December 31th 2023, were included. Data on demographics, treatment, and outcomes were also collected. A pooled analysis of 5-year overall survival (OS) was performed. Nineteen articles and 1488 patients met the inclusion criteria. The first-choice treatment strategy was surgery (74.5%), whereas adjuvant radiotherapy was administered to 56.7% of the patients. The follow-up range was 6– 390 months. A total of 552 deaths were recorded, 98.7% of which were cancer related. The 5-year OS rate ranged from 28.6% to 100.0%; in the pooled analysis, it was 65% (range, 32%– 96%). Surgery remains the mainstay of treatment for TACC. Adjuvant radiotherapy is commonly administered to patients with positive margins, and survival estimates are good overall but heterogeneous.Keywords: adenoid cystic carcinoma, trachea, treatment, survival